The Influence Of Environmental Performance And Environmental Costs On Firm Value With Corporate Social Responsibility Disclosure As A Moderating Variable - Wilhelmina Sir, Serlinha; Dwija Putri, I Gusti Ayu Made Asri (Journal of Management Economic and Financial, 2025)
The purpose of this study is to determine the effect of environmental performance and environmental costs on company value with corporate social responsibility disclosure as a moderating variable. The population of companies is manufacturing companies listed on the Indonesia Stock Exchange in 2021-2023. Research data was obtained from the Indonesia Stock Exchange website and the websites of each company. The analysis method used is Moderating Regression analysis using SPSS 26.0 software. The results of the study indicate that environmental performance has a negative and significant effect on firm value. Environmental costs have a positive and significant effect on firm value. CSRD is able to moderate by weakening the effect of environmental performance on firm value. CSRD is able to moderate by strengthening the effect of environmental costs on firm value.